Strategi Komunikasi J&T Express Dalam Pelayanan Transaksi Cod ( Cash On Delivery )Di Kota Solok - ., Asyha; Edlina, Ria (CV. ITTC INDONESIA, 2024)
The COD (Cash On Delivery) payment method is a payment that can be made after the buyer or recipient of the goods has received the goods ordered. With the convenience that people get in online shopping activities, online shopping is becoming more and more popular among people, one of which is in the city of Solok. And one of the expeditions in Solok City which is a place for sending goods to Solok is J&T Express. There are problems caused by customers' ignorance of online buying and selling mechanisms that use the COD payment method, causing problems for couriers and customers during the transaction process. For this reason, J&T Express has a strategy in processing COD transactions with customers. The research method used in this research is a qualitative descriptive approach and uses Joseph Devito's theory to analyze the communication process of J&T Express's strategy in transaction services via COD. The result of this research is that J&T Express provides education to couriers to provide information to COD customers about rules, policies and procedures for handling complaints such as complaints about ordered goods using the COD payment method. Apart from that, regulations regarding COD payment methods are also available on the internet so that many COD customers can know them. In this strategy, there are obstacles that make it difficult for COD customers to receive information, namely the lack of courier education to customers about COD regulations, the existence of limited customer technology, and also customer disagreement with the rules.